I.YUSUPOVTIŃ “DALA ÁRMANLARI” SHIǴARMASINDA METAFORALARDIŃ STILLIK QOLLANILIWI - Allanazarov, E.; Erejepova, Q. (SCIENCE and SOCIETY, 2023)
In article, one of the linguistic units of our language is devoted to the event of the use of metafora units in an artistic language. In the works of I’ Yusupov, some details are given concerning the peculiarities of the meaning of the word in use.